The Downfall of an Institution - Atrocities of Power and Politics - Nair, Manju (IIUM Journal of Case Studies in Management, 2019)
Abstract The case is about an educational institution which went to oblivion because of the conflicting interests, power bases and coalitions arising out of organisational politics and poor Leadership. An Institution which was initiated by one of the best educational groups in Rajasthan which is running successfully many renowned educational institutions including a university had to eventually close down because of the errors in the thought and action in the politics of organizational life.